ANALISIS SISTEM PEMBUMIAN TOWER SALURAN TRANSMISI DARI GARDU INDUK KAPAL – GARDU INDUK GIANYAR - Satya Wicaksana, IGP Agung; Arta Wijaya, IW; Janardana, IGN (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
This study aims to improve the earthing value of transmission lines which have an earth value less than the standard value off SPLN No 121: 1996, namely 10 and recommend an earthing system that meets the standards. Theemethodduseddissa descriptive method by calculating the value of the earthing system by following the SPLN standard No. 121: 1996. This analysis consists of several stages, namely a site survey, measuring soil resistance (R) to calculate the value of soil resistivity (?) then calculating the value of grounding resistance with 5 types of grounding systems to achieve grounding resistance 10 , namely one electrode grounding system, 2 electrode grounding system planted vertically S > L, 2 electrode earthing system planted vertically S < L, plate earthing system, and a grid-rod earthing system. The results of the research are for paddy fields using a vertical one-electrode earthing system, the value is 7.32 ? with a manufacturing cost of Rp. 857,000, on farmland with a vertical oneelectrode earthing system, the value is 8.36 ? with a manufacturing cost of Rp. 1,363,000, and on clay soil with a vertical one-electrode earthing system, the result is 7.98 ? with a manufacturing cost of Rp. 857,000.